Management of subgingival fractured tooth - Nidhi Singh; T P Chaturvedi; Chi Koy Wang (Wolters Kluwer Medknow Publications, 2019)
Traumatized anterior teeth along with subgingival crown fractures are challenge to treat. Management of subgingival fractures includes exposing the cervical margin, above the gingiva followed by appropriate coronal restoration. The treatment modalities, which involve exposing the cervical margin, are surgical crown lengthening or by orthodontic extrusion. Orthodontic extrusion of subgingival fractured maxillary anterior tooth was done in this case report after endodontic treatment followed by esthetic rehabilitation which was yet conservative and cost - effective.